Internalization of National Insight in Preventing the Spread of Radicalism: A Study of the Khilafatul Muslimin Group in Lampung Province - Firsada, Muhammad; Nasor; Bahrudin, Moh.; Setiawati, Rini (Analisis: Jurnal Studi Keislaman, 2025)
The spread of transnational ideology-based radicalism poses a serious challenge to the ideological resilience and integrity of the Unitary State of the Republic of Indonesia (NKRI), including in Lampung Province. The Khilafatul Muslimin group is one of the religious groups that carries an alternative ideological narrative that has the potential to weaken national insight. Therefore, this study aims to analyze the process of internalizing national insight as a strategy to prevent the spread of radicalism within the Khilafatul Muslimin group in Lampung Province. This study uses a qualitative approach with a descriptive-analytical design. Data collection was conducted through in-depth interviews with key informants, observation, documentation studies, and relevant literature reviews. Data analysis was conducted thematically through the stages of data reduction, data presentation, and drawing conclusions. The results show that internalization of national insight is effective when implemented through a persuasive, dialogical, and sustainable approach that involves state and social actors collaboratively. The integration between the socialization of state ideology and the Islamic community development approach has proven capable of building inclusive ideological awareness, strengthening ideological resilience, and encouraging the transformation of religious understanding in line with Pancasila and the NKRI. The novelty of this research lies in the findings of a model of internalization of national insight based on community participation, the role model of religious figures, and the strategic role of former members of radical groups as agents of change in preventing radicalism that is more humanistic and sustainable.